Analisis Penerapan Good Governance dalam Mendukung Kualitas Laporan Keuangan Pemerintah - M Irham Ardiansyah S; Annisa Khairiah; Ariyanta Maulana Sitepu; Morina Simanjorang; Galih Supraja (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze the implementation of Good Governance in supporting the quality of government financial reports through the results of several previous studies. This study uses a qualitative research method with a descriptive approach by analyzing and reviewing literature studies from several previous studies, this study uses secondary data by collecting data and results of previous studies related to the implementation of Good Governance on the quality of government financial reports through the Google Scholar website. In the discussion of this study, there are eleven results from eleven previous research journals that were analyzed with the results that there are eight studies that state that the implementation of Good Governance has a positive effect on the quality of government financial reports, two studies that state that the implementation of Good Governance does not have a positive effect on the quality of government financial reports, and one study states that the implementation of Good Governance has a positive but not significant effect on the quality of government financial reports. Based on the results of this study, it can be concluded that the implementation of Good Governance has a positive effect in supporting the quality of government financial reports.